2000
DOI: 10.1128/cdli.7.5.734-738.2000
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Chlamydia pneumoniae and Mycoplasma pneumoniae Immunoglobulin G and A Antibodies in a Healthy Finnish Population as Analyzed by Quantitative Enzyme Immunoassays

Abstract: Chlamydia pneumoniae and Mycoplasma pneumoniae immunoglobulin G (IgG) and IgA antibody seroprevalence rates and antibody levels related to age and gender were studied. The samples (n ‫؍‬ 742) were collected during a nonepidemic period and analyzed by quantitative enzyme immunoassays (EIAs). Seroprevalence to C. pneumoniae was found to increase sharply in young children, and in the 15-to 19-year-old group it reached levels as high as 70 and 60% for IgG and IgA, respectively. After adolescence, seroprevalence sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
31
2
7

Year Published

2002
2002
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(48 citation statements)
references
References 13 publications
8
31
2
7
Order By: Relevance
“…The use of an IgG-removing reagent before the measurement of IgA antibodies in EIA would be worth testing. In both tests, IgG and IgA antibodies increase in older age but at different rates (13,45).…”
Section: Discussionmentioning
confidence: 99%
“…The use of an IgG-removing reagent before the measurement of IgA antibodies in EIA would be worth testing. In both tests, IgG and IgA antibodies increase in older age but at different rates (13,45).…”
Section: Discussionmentioning
confidence: 99%
“…Serologic analysis, particularly microimmunofluorescence tests, has been extensively used; however, interpretation is problematic, since a large part of the population has preexisting immunoglobulin G antibodies from a previous exposure(s) (47). In addition, serologic methods are subjective, and there is considerable cross-reaction with other species of Chlamydia and with Bartonella (24,30,35,47). Due to the difficulties with culturing and serologic analysis, a number of nucleic acid amplification assays for detecting C. pneumoniae have been developed (6).…”
mentioning
confidence: 99%
“…The independent association between elevated C. pneumoniae IgA antibody levels and fibrinogen levels further indicates that chronic infections could be of importance for disease activity (25). However, several studies have failed to show any association between C. pneumoniae-specific IgA antibodies and chronic lung or cardiovascular diseases (2,3,23,26,28). The present results clearly indicate that there are large variations in the abilities of different commercial anti-IgA FITC conjugates to detect IgA antibodies in serum.…”
Section: Discussionmentioning
confidence: 53%
“…IgA antibodies to C. pneumoniae measured by MIF tests seem to be rare in children (unpublished data), and low IgA prevalences have also been found when antibodies to chlamydial lipopolysaccharide have been measured by EIAs (12), even in children found positive for C. pneumonie by culturing or PCR. Tuuminen et al recently reported very high IgA antibody prevalences in Finnish children over 4 years old by using a commercial EIA method for C. pneumoniae, but their method has not been validated by comparison to MIF tests performed in an experienced laboratory (26). It is possible that small children do not frequently produce IgA antibodies as a response to primary upper respiratory tract infections and that IgA responses are generally more common in reinfections, which are more common in adults (5,22).…”
Section: Discussionmentioning
confidence: 99%